Critically ill patients with COVID-19 in Tokyo, Japan: A single-center case series - Miike, Satoshi (J Infect Chemother, 2021)
INTRODUCTION: We reported, in our previous study, a patient with coronavirus disease 2019 (COVID-19) who was successfully treated with extracorporeal membrane oxygenation. Data on clinical courses and outcomes of critically ill patients with COVID-19 in Japan are limited in the literature. This study aimed to describe the clinical courses and outcomes of critically ill patients with COVID-19 in Tokyo, Japan. METHODS: This is a single-center case series study. Patients with COVID-19 treated with mechanical ventilation (MV) were reviewed retrospectively. Data on baseline characteristics, in-hospital treatment, and outcomes were collected. RESULTS: Between February 2, 2020, and June 30, 2020, 14 critically ill patients with COVID-19 were treated with MV. Most patients were male and had comorbidities, especially hypertension or diabetes; 35.7% were overweight and 21.4% were obese. The majority of the patients had dyspnea on admission. The median duration of MV was 10.5 days, and the 28-day mortality rate was 35.7%. In the four patients with COVID-19 who died, the cause of death was respiratory failure. CONCLUSIONS: As in previous reports from other countries, the mortality rate of patients with COVID-19 requiring intensive care remains high in Tokyo. Further study on the appropriate timing of MV initiation and specific treatments for critically ill patients with COVID-19 is needed.